A phylogenetic analysis of the tribe Zopherini with a review ofthe species and generic classification (Coleoptera: Zopheridae) - Foley, Ian A.; Ivie, Michael A. (Zootaxa, 2008)
A morphology-based phylogenetic analysis of all known species (excluding the well-revised Zopherus Gray) of the tribe Zopherini was performed. The genus Sesaspis Casey is elevated from synonymy, redescribed and two new species are described from Central America, Sesaspis ashei NEW SPECIES and Sesaspis triplehorni NEW SPECIES. The following NEW COMBINATIONS are proposed: Noserinus furcatus (Kirsch), Phloeodes venustus (Champion), Sesaspis emarginata (Horn), Sesaspis lutosa (Champion), Sesaspis sylvatica (García-París et al.), and Sesaspis doyeni (García-París et al.). The following NEW SYNONYMIES are proposed: Phloeodes pustulosus LeConte of Phloeodes diabolicus LeConte, Nosoderma prominens Casey, Nosoderma senex Casey, Nosoderma brevicollis Casey, and Nosoderma subglabrus Casey of Eurychora inaequale Say as Verodes inaequalis (Say), Nosoderma insigne Champion of Nosoderma interruptum Champion as Verodes interruptus (Champion), Noserodes squalidus Casey of Nosoderma guatemalense Champion as Verodes guatemalensis (Champion), Scoriaderma congolense Fairmaire of Nosoderma scabrosum Solier as Verodes scabrosus (Solier), and Scoriaderma comoriense Fairmaire of S. cordicolle Waterhouse. A revised key to the world genera is provided, as well as keys to all species of the tribe, save those of Zopherus, including the multispecies genera Noserinus Casey, Nosoderma Guérin-Méneville, Phloeodes LeConte, Sesaspis Casey, and Verodes Casey. A synoptic catalog of the described species is provided, with brief comments on the taxonomic histories of the tribe, genera, and species. All recognized species are illustrated and diagnosed, with information on their types, taxonomic history and geographic distributions.